2015
DOI: 10.1214/ejp.v20-3777
|View full text |Cite
|
Sign up to set email alerts
|

The diameter of an elliptical cloud

Abstract: We study the asymptotic behavior of the diameter or maximum interpoint distance of a cloud of i.i.d. d-dimensional random vectors when the number of points in the cloud tends to infinity. This is a non standard extreme value problem since the diameter is a max U -statistic, hence the maximum of dependent random variables. Therefore, the limiting distributions may not be extreme value distributions. We obtain exhaustive results for the Euclidean diameter of a cloud of elliptical vectors whose Euclidean norm is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In the unbounded case, Henze and Lao [6] obtained a (non-Gumbel) limit distribution of M n if the distribution of Z is power-tailed spherically decomposable. Finally, Demichel et al [4] proved several results for the diameter of an elliptical cloud with unbounded support.…”
Section: Introductionmentioning
confidence: 92%
“…In the unbounded case, Henze and Lao [6] obtained a (non-Gumbel) limit distribution of M n if the distribution of Z is power-tailed spherically decomposable. Finally, Demichel et al [4] proved several results for the diameter of an elliptical cloud with unbounded support.…”
Section: Introductionmentioning
confidence: 92%
“…For the unbounded support case, Henze (2010) showed that the limiting distribution of M n is not of the Gumble type if the distribution of X is power-tailed spherically decomposable. Demichel et al (2015) consider the elliptical distributions with unbounded support. In the case of bounded support, Tang et al (2022) provide a comprehensive review of the current body of literature.…”
Section: Introductionmentioning
confidence: 99%